Gambaran Kadar Hemoglobin dan Hematokrit pada Pasien Stroke Iskemik Berusia 15-64 Tahun di RSUP Prof. Dr. R. D. Kandou - Malingkas, Lingkanwene T. D.; Wowor, Mayer F.; Berhimpon, Siemona L. E. (e-CliniC, 2024)
Abstract: Ischemic stroke is the most common stroke and represents 80% of stroke cases. Stroke causes an increase in blood viscosity, thus inhibiting blood flow which has an impact on the body's normal function which can be seen from the hemoglobin and hematocrit levels. This study aimed to determine the description of hemoglobin and hematocrit levels in ischemic stroke patients aged 15-64 years treated at Prof. Dr. R. D. Kandou Hospital. This was a retrospective and descriptive study using secondary data taken from medical records. The results obtained 47 patients that met the inclusion criteria, consisting of 29 male patients (61.7%) and 18 female patients (38.3%). Based on stroke classification, most patients were in acute phase (87.2%). Normal hemoglobin levels were more often found in the age of 46-55 years, meanwhile decreased hematocrit levels were more often found in the age of 56-65 years (23.4%).  In conclusion, normal hemoglobin level and decreased hematocrit level are more often found in acute ischemic stroke patients. Keywords: ischemic stroke; hemoglobin; hematocrit    Abstrak: Stroke iskemik merupakan stroke yang paling sering terjadi dan mewakili 80% kasus stroke. Stroke mengakibatkan peningkatan kekentalan/viskositas darah, sehingga menghambat aliran darah yang berdampak pada fungsi normal tubuh yang dapat dilihat dari hasil pemeriksaan kadar hemoglobin dan hematokrit. Penelitian ini bertujun untuk mengetahui gambaran kadar hemoglobin dan hematokrit pada pasien stroke iskemik berusia 15-64 tahun yang dirawat di RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data sekunder yang diambil dari rekam medis. Hasil penelitian mendapatkan 47 pasien stroke iskemik yang memenuhi kriteria inklusi, terdiri dari 29 pasien laki-laki (61,7%) dan 18 pasien perempuan (38,3%). Berdasarkan klasifikasi stroke, pasien terbanyak pada fase akut (87,2%). Kadar hemoglobin normal lebih sering didapatkan pada kelompok usia 46-55 tahun (44,7%) sedangkan kadar hematokrit menurun lebih sering didapatkan pada kelompok usia 56-65 tahun (23,4%). Simpulan penelitian ini ialah kadar hemoglobin normal dan kadar hematokrit menurun sering didapatkan pada pasien stroke iskemik akut. Kata kunci: stroke iskemik; hemoglobin; hematokrit